Leptonic/hadronic models for electromagnetic emission in microquasars: the case of GX 339-4 - Romero, Gustavo Esteban (2010)
We present a general self-consistent lepto/hadronic jet model for the non-thermal electromagnetic emission of microquasars. The model is applied to the low-mass microquasar (LMMQ) GX 339-4 and predicts its high-energy features. We assume that both leptons and hadrons are accelerated up to relativistic energies by diffusive shock acceleration, and calculate their contribution to the electromagnetic spectrum through all main radiative processes. The radiative contribution of secondary particles (pions, muons and electron-positron pairs) is included. We use a set of simultaneous observations in radio and X-rays to constrain the model parameters and find the best fit to the data. We obtain different spectral energy distributions that can explain the observations, and make predictions for the high-energy emission. Observations with gamma-ray instruments like Fermi can be used to test the model and determine the proton content of the jets. Finally, we estimate the positron injection in the surrounding medium. Our findings support the suggested association between LMMQs and the observed distribution of the 511 keV line flux observed by INTEGRAL.